Preliminary study on pelletization of oil palm empty fruit bunches (EFB)/spent activated carbon (AC): Effect of mixing and adhesive ratio - Teo, K. Y.; Suriati, Ghazali; Syarifah, Abd Rahim (Universiti Malaysia Pahang, 2021)
Non-renewable resources such as fossil fuels could be combusted for energy and electricity to human kind. The demand of fossil fuel energy had reached an exponential growth which caused disasters and catastrophic damages on the environment; thus, renewable resources should be implemented to protect the environment. One of the natural resources was biomass waste. In this study, spent activated carbon (AC) was co-pelletized with biomass waste, oil palm empty fruit bunches (EFB). The effect of EFB, AC and adhesive (tapioca) mixing ratio in the pellet was evaluate through physical and thermal properties. The raw materials were grinded and mixed together at different AC/EFB/tapioca ratio. The mixed raw materials were compressed at 130°C and 7 MPa for 10 minutes. The densified products were characterized by using Thermogravimetric Analysis (TGA). For the thermal characteristics, sample with 0% waste AC, 90% EFB and 10% starch had the highest mass loss rate (570 µg/min) followed by sample with 10% of waste AC, 60% of EFB and 30% of starch which was 420 µg/min. Besides, sample with 0% waste AC, 90% EFB and 10% had the highest burn out temperature (802.6 °C) followed by sample with 30% of waste AC, 60% of EFB and 10% of starch which was 792.85 °C. In conclusion, sample with 0% waste AC, 90% EFB and 10% starch had an easiest ignition and longest combustion period since it had the highest mass loss rate and burn out temperature.